A Truly Existing “Extradisciplinary” Architecture Design System ——Analysis and Discussion on Ancient Chinese Architecture Practice Based on Algorithms (EAAE Annual Conference Proceedings, 2023)
In the context of Western culture, Architecture is usually regarded as an independent discipline with its own boundaries. Researchers either try to dig inward within the boundaries or seek intersections outside the boundaries. But in another context, in ancient China, the design of architecture was based on algorithms (a branch of mathematics), which is obviously an independent system of extra-disciplinary.